2019
DOI: 10.1140/epjc/s10052-019-7360-9
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Tolman VII solution by gravitational decoupling

Abstract: Using the gravitational decoupling by the minimal geometric deformation approach, we build an anisotropic version of the well-known Tolman VII solution, determining an exact and physically acceptable interior two-fluid solution that can represent behavior of compact objects. Comparison of the effective density and density of the perfect fluid is demonstrated explicitly. We show that the radial and tangential pressure are different in magnitude giving thus the anisotropy of the modified Tolman VII solution. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(61 citation statements)
references
References 76 publications
2
59
0
Order By: Relevance
“…To close, we have observed that in the presence of plasma medium, the deflection angle of BH decreases as compared to BH in the vacuum. As compared with these papers ([20]- [28]), we have also confirmed the results that deflection angle reduces more in plasma medium as compared to vacuum cases. The authors of [28], show that the radius of shadow of the black hole is increasing, when the plasma parameter increases, so that in future we will study the plasma effect on shadow of non-electrodynamics black hole.…”
Section: Deflection Angle Wrt Bh Chargesupporting
confidence: 89%
See 1 more Smart Citation
“…To close, we have observed that in the presence of plasma medium, the deflection angle of BH decreases as compared to BH in the vacuum. As compared with these papers ([20]- [28]), we have also confirmed the results that deflection angle reduces more in plasma medium as compared to vacuum cases. The authors of [28], show that the radius of shadow of the black hole is increasing, when the plasma parameter increases, so that in future we will study the plasma effect on shadow of non-electrodynamics black hole.…”
Section: Deflection Angle Wrt Bh Chargesupporting
confidence: 89%
“…Moreover, Chakrabarty et al [26] and Atamurotov et al [27] have also studied the plasma medium's effect on gravitational lensing and on shadow of black hole. Moreover, Hensh et al [28] have calculated the gravitational lensing of Kehagias-Sfetsos compact objects in the presence of plasma medium.…”
Section: Introductionmentioning
confidence: 99%
“…Refs. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] include and study anisotropic solutions of quasi-Einstein's equations, in the context of the MGD procedure [37]. Besides, anisotropic a e-mail: roldao.rocha@ufabc.edu.br (corresponding author) b e-mails: anderson_tomaz@id.uff.br; anderson.tomaz@ufabc.edu.br MGD-decoupled solutions were obtained by gravitational decoupling methods [38][39][40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the maximum compactness of neutron stars in general relativity is higher than that in scalar-tensor gravity when the coupling constant is confined to values provided by astronomical observations. Hensh and Stuchlík [50] have started from the isotropic Tolman VII perfect fluid solution and by using the MGD method they have got a new exact and analytical solution. This new solution represents the anisotropic version of the Tolman VII solution, which satisfies all criteria for physical acceptability.…”
Section: Introductionmentioning
confidence: 99%